Shape in medical imaging : International Workshop, ShapeMI 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 20, 2018, Proceedings /: International Workshop, ShapeMI 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 20, 2018, Proceedings. (2018) - Unknown
No abstract available